2007
DOI: 10.1001/archneur.64.6.836
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokine Gene Polymorphisms and Increased Risk of Parkinson Disease

Abstract: Background:The proinflammatory cytokines tumor necrosis factor ␣ (TNF-␣) and IL-1␤ (interleukin 1␤) have a role in neuroinflammation, and functional polymorphisms in the TNF-α and IL-1β genes may affect susceptibility to Parkinson disease (PD).Objective: To investigate whether functional DNA polymorphisms of the TNF-α and IL-1β genes affect the risk of PD.Design: Population-based case-control study.Setting: Three rural California counties (Fresno, Tulare, and Kern).Participants: Two hundred eighty-nine inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 24 publications
6
71
1
Order By: Relevance
“…This result is consistent with the majority of previous studies (22)(23)(24)(25)(26)(27), and only one study presented an opposing conclusion (21). In comparison to the former studies, the meta-analysis showed a stronger power and involved subgroup analyses by genetic models and ethnicity, which allowed for a more stable and comprehensive conclusion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with the majority of previous studies (22)(23)(24)(25)(26)(27), and only one study presented an opposing conclusion (21). In comparison to the former studies, the meta-analysis showed a stronger power and involved subgroup analyses by genetic models and ethnicity, which allowed for a more stable and comprehensive conclusion.…”
Section: Discussionsupporting
confidence: 90%
“…A study was also found from the references in the retrieved literature. Finally, 15 eligible studies (16 stages) (13,14,(16)(17)(18)(19)(21)(22)(23)(24)(25)(26)(27)(28)(29) were included in the meta-analyses (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a number of proinflammatory mediators, such as cytokines, and inflammatory-associated factors such as cyclooxygenase-2 (COX-2) and inducible-nitric oxide synthase (iNOS) are elevated in the CNS or cerebrospinal fluid of neurodegenerative disease patients. Furthermore, recent epidemiological studies indicate that the chronic use of nonsteroidal anti-inflammatory agents (NSAIDs) reduces the risk of PD and AD ( [39,152,154,225]) and inheritance of polymorphisms resulting in enhanced expression of various inflammatory mediators was reported to increase the risk of these two pathologies ( [32,246]). Importantly, activated microglia were found at the histopathological sites of several brain disorders, including neurodegenerative diseases such as AD, MS, PD, ALS (amyotrophic lateral sclerosis) and AIDS-associated dementia ( [56,93,116,153] and [192]).…”
Section: Role Of Microglia In Neurodegenerationmentioning
confidence: 99%
“…PD, Alzheimer's disease, multiple sclerosis, Huntington's disease, amyotrophic lateral sclerosis, tauopathies and age-related macular degeneration are all associated with chronic neuroinflammation and elevated levels of several cytokines. 12,[31][32][33][34][35][36][37][38][39][40] In addition, there are several recent reports that show normal aging is accompanied by progressive alterations in immune function. 41 Increased innate immune activity, microglial and immune cell activation and increased pro-inflammatory cytokine expression/release are found in brains of patients with PD and inflammation is thought to be a major contributor to the ongoing neurodegeneration and disease progression.…”
Section: Current Understanding Of the Immune Responses In The Cnsmentioning
confidence: 99%